Language assessment and the inseparability of lexis and grammar: Focus on the construct of speaking. (October 2017) - Römer, Ute
This paper aims to connect recent corpus research on phraseology with current language testing practice. It discusses how corpora and corpus-analytic techniques can illuminate central aspects of speech and help in conceptualizing the notion of lexicogrammar in second language speaking assessment. The description of speech and some of its core features is based on the 1.8-million-word Michigan Corpus of Academic Spoken English (MICASE) and on the 10-million-word spoken component of the British National Corpus (BNC). Analyses of word frequency and keyword lists are followed by an automatic extraction of different types of phraseological items that are particularly common in speech and serve important communicative functions. These corpus explorations provide evidence for the strong interconnectedness of lexical items and grammatical structures in natural language. Based on the assumption that the existence of lexicogrammatical patterns is of relevance for constructs of speaking tests, the paper then reviews rubrics of popular high-stakes speaking tests and critically discusses how far these rubrics capture the central aspects of spoken language identified in the corpus analyses as well as the centrality of phraseology in language. It closes with recommendations for speaking assessment in the light of this characterization of real-world spoken lexicogrammar.